2017
DOI: 10.1002/open.201700065
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Emitting Agents for Noninvasive Assessment of Kidney Function

Abstract: The noninvasive assessment of kidney function and diagnosis of kidney disease have long been challenges. Traditional methods are not routinely available, because the existing protocols are cumbersome, time consuming, and invasive. In the past few years, significant progress in the area of diagnosing kidney function and disease on the basis of light‐emitting agents has been made. Herein, we briefly review light‐emitting agents, including organic fluorescent agents and inorganic renal clearable luminescent nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 88 publications
0
14
0
Order By: Relevance
“…Performing contralateral nephrectomy when the injured kidney is functioning optimally reduces animal suffering and improves survival. It also enables transdermal FITC-Sinistrin clearance to be measured, which is quicker to perform than MSOT and has the advantage that it can be undertaken in awake animals 16,31 . Therefore, the CKD model was refined by performing contralateral nephrectomy on day 14 after R-IRI (Supplementary Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Performing contralateral nephrectomy when the injured kidney is functioning optimally reduces animal suffering and improves survival. It also enables transdermal FITC-Sinistrin clearance to be measured, which is quicker to perform than MSOT and has the advantage that it can be undertaken in awake animals 16,31 . Therefore, the CKD model was refined by performing contralateral nephrectomy on day 14 after R-IRI (Supplementary Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
“…Whilst it is not appropriate to use IRDye clearance to calculate GFR, due to its high levels of protein binding 16,25 , it can be used as a surrogate measure of renal function due to its sole excretion through the glomeruli. After assessment of IRDye PK, we found that t max is the parameter that best distinguishes the injured from the uninjured kidney.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kidney is the primary site for metabolism and excretion of metabolic products and therapeutic drugs, thus it is vulnerable to injury. 51 As such, real-time monitoring of kidney dysfunction is essential in clinical practice. To date, ‘always on’ probes such as CdSe/ZnS core–shell quantum dots, 52 silica Cornell dots 53 and zwitterionic fluorophore ZW800, 54 gold nanoclusters (AuNPs), 55 etc.…”
Section: Kidney Diseasesmentioning
confidence: 99%
“…Advancements have been seen at three level fabrications of new nanomaterials, coatings and discovery of new drug delivery vehicles for biodistribution of therapeutic agents deep into the kidney tissues. Still there is a need for of new strategies regarding the design of ideal glomerular filtration rate agents and renal clearable nanoparticles [13]. There is a need to reduce material toxicities of nano-devices, to make them non-invasive when used for restoration of kidney function and diagnosis of disease.…”
Section: Use Of Nanoparticlesmentioning
confidence: 99%